2021
DOI: 10.1002/cssc.202100926
|View full text |Cite
|
Sign up to set email alerts
|

Dual Valorization of Lignin as a Versatile and Renewable Matrix for Enzyme Immobilization and (Flow) Bioprocess Engineering

Abstract: Lignin has emerged as an attractive alternative in the search for more eco‐friendly and less costly materials for enzyme immobilization. In this work, the terephthalic aldehyde‐stabilization of lignin is carried out during its extraction to develop a series of functionalized lignins with a range of reactive groups (epoxy, amine, aldehyde, metal chelates). This expands the immobilization to a pool of enzymes (carboxylase, dehydrogenase, transaminase) by different binding chemistries, affording immobilization yi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

6
1

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 47 publications
2
23
0
Order By: Relevance
“…[30] Such control also proved to be successful for GA (Figure 2c). The correlation between the amount of GA used during the fractionation reaction versus the mmol of carboxylic acids quantified on the extracted lignin by 31 P NMR was close to linear before reaching a plateau at around 6.5 mmol of GA g À 1 of dry biomass, similarly to what we observed in the case of TALD-lignin, [30] confirming the potential of controlling the chemical functionalities of lignin during the extraction process.…”
Section: Extraction and Characterization Of Glyoxylic Acid-functional...supporting
confidence: 80%
See 2 more Smart Citations
“…[30] Such control also proved to be successful for GA (Figure 2c). The correlation between the amount of GA used during the fractionation reaction versus the mmol of carboxylic acids quantified on the extracted lignin by 31 P NMR was close to linear before reaching a plateau at around 6.5 mmol of GA g À 1 of dry biomass, similarly to what we observed in the case of TALD-lignin, [30] confirming the potential of controlling the chemical functionalities of lignin during the extraction process.…”
Section: Extraction and Characterization Of Glyoxylic Acid-functional...supporting
confidence: 80%
“…[29] Moreover, when multifunctional aldehydes are used, it is consequently possible to introduce chemical functionalities on the lignin backbone that were not present in its original structure, tuning therefore the final properties of the isolated material. [30,31] Here, we take advantage of the AAF process to extract lignin in presence of glyoxylic acid (GA), in order to produce a lignin (GA-lignin) containing a controlled amount of carboxylic acids on its polymeric chains, in a single step from lignocellulosic biomass (Figure 1d). This process allowed us to avoid performing post-isolation functionalization reactions, which are typically necessary when technical lignins are used in material applications.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In some of our previous works, we have observed a similar phenomenon when using non-polar substrates that can interact with hydrophobic supports. 36,37 Therefore, we can conclude that SHC-catalyzed reactions are not particularly compatible with carriers used to immobilize the biocatalyst. As an innovative alternative, we developed the concept of crosslinked spheroplasts (CLS), which overcomes the stability and reusability issues of the catalysts, it avoids any interaction between the substrates/products and the carrier, and of course also eliminates costs and waste management linked to the use of a carrier (Fig.…”
Section: Discussionmentioning
confidence: 95%
“…[12] Recently, we have demonstrated that by extracting lignin in presence of aldehydes, the condensation and repolymerization reactions could be avoided by the formation of stable acetals on the β-O-4 linkages, in a process known as Aldehyde-Assisted Fractionation (AAF) (Figure 1a). [13,14] We also showed that multifunctional aldehydes could be employed to simultaneously extract and functionalize lignin at high yields which could facilitate its use as a surfactant or for further functionalization for use in resins. [15,16] For multiple high-end material applications including soft tissue engineering, the targeted material must not only be biocompatible, but must also present well-defined rheological and other mechanical properties.…”
Section: Introductionmentioning
confidence: 94%